Piagam Madinah dan Spiritnya dalam Undang-Undang Dasar (UUD) 1945 - Elkhairati Elkhairati (Institut Agama Islam Negeri Curup, 2019)
This paper aims to look at the existence of the Medina Charter in terms of history, content and authenticity and how it is spiritual in the 1945 Constitution. This study takes the form of literature with a content analysis approach. Data collection techniques in this study are carried out by collecting magazines, journals and books and utilizing internet to collect data related to research. This study concludes that the Charter of Medina contains the Islamic Shari'a as a law, is democratic in nature. If observed carefully, it will be seen the spirit of the Medina Constitution in the 1945 Constitution as the basis of the State of Indonesia. The concrete form is reflected in the points of the articles of the 1945 Constitution. This proves that even though the Republic of Indonesia is not an Islamic state, it does not mean that this country ignores Islamic shari'a.